2004
DOI: 10.1080/09593332508618390
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Dyes using Peat: Equilibrium and Kinetic Studies

Abstract: In recent years, adsorption has been accepted as one of the most appropriate processes for decolorization of wastewaters. This paper presents experimental results on application of peat for removal of structurally diverse dyes (azo, oxazine, triphenylmethane, thiazine and others) with emphasis on relevant factors such as the adsorbate-adsorbent chemical properties and chemical interaction as well as adsorption conditions. The equilibrium experimental results were fitted to Langmuir and Freundlich isotherms to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 17 publications
0
12
0
2
Order By: Relevance
“…These may be compared with literature values for derived and commercial activated carbons; for AB 1, reported capacities are 25 (Sepulveda et al 2004), 18 (Annadurai et al 2002) and 1.73 mg g −1 (Koumanova et al 2003), and for AB 113, reported capacities are 219 (Jain et al 2003), 30 (Koumanova et al 2003), 310 (Faria et al 2004) and 2.1 (Jain et al 2003). The widely used commercial water treatment activated carbon F400 only had capacities of 101, 101 and 129 mg g −1 for three acid dyes, namely Polar Blue RAWL, Acid Red 114 and Polar Yellow, respectively (Choy et al 1999).…”
Section: Equilibrium Isothermsmentioning
confidence: 99%
“…These may be compared with literature values for derived and commercial activated carbons; for AB 1, reported capacities are 25 (Sepulveda et al 2004), 18 (Annadurai et al 2002) and 1.73 mg g −1 (Koumanova et al 2003), and for AB 113, reported capacities are 219 (Jain et al 2003), 30 (Koumanova et al 2003), 310 (Faria et al 2004) and 2.1 (Jain et al 2003). The widely used commercial water treatment activated carbon F400 only had capacities of 101, 101 and 129 mg g −1 for three acid dyes, namely Polar Blue RAWL, Acid Red 114 and Polar Yellow, respectively (Choy et al 1999).…”
Section: Equilibrium Isothermsmentioning
confidence: 99%
“…The experimental equilibrium data can be fit adequately by both models (correlation coefficients [0.99). The values of maximum adsorption capacity of AB1 onto banana peel, which depends on the particle size, are in the range 250-620 mg g -1 ; whereas, in other bioadsorbents such as magellanic moss peat [44] and cells fodder yeast (Kluyveromyces fragilis) magnetically modified [45], the maximum adsorption capacity of AB1 reported, is in the range of 25.0 and 29.8 mg g -1 , respectively. The maximum adsorption capacity increases 20% when the particle diameter decreases by half, while the effect is not significant for k L constant.…”
Section: Adsorption Of Acid Black 1 Dyementioning
confidence: 93%
“…On the contrary, for the same temperature change, interaction energy parameter (b) decreased from 0.295 to 0.176 (L/g) and from 0.132 to 0.109 (L/g) for WS and CCLs, respectively. These values state that the dye presents a strong interaction with the active sites of the 1920 L.A. Sepúlveda et al [69,70]. The fit parameters of adsorption experimental data using the Freundlich model are shown in Table 4, whose correlation coefficients (R 2 ) vary from 0.63 to 0.88.…”
Section: Adsorption Isothermmentioning
confidence: 98%